1989
DOI: 10.1152/ajpgi.1989.257.1.g169
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine analogues L365,260 and L364,718 as gastrin and pancreatic CCK receptor antagonists

Abstract: We examined the ability of the recently described 3-(benzoylamino)benzodiazepine analogue L365,260 and the 3-(acylamino)benzodiazepine analogue L364,718 to distinguish gastrin from pancreatic cholecystokinin (CCK) receptors. Neither L365,260 nor L364,718 when present alone (1 microM) caused stimulation of amylase release from guinea pig pancreatic acini or caused contraction of smooth muscle cells from guinea pig stomach. Each analogue inhibited CCK-stimulated amylase release, gastrin-17-I-stimulated smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 0 publications
1
30
1
Order By: Relevance
“…The data obtained in this study disagree with the observations made in isolated cell preparations wherein the CCKA selective antagonist, devazepide, was more powerful than L-365,260 at inhibiting the contractile responses to gastrin (Grider & Makhlouf, 1990). However, the data are in agreement with those obtained in a similar isolated cell preparation in which L-365,260 was more powerful than devazepide at blocking the contractile effects of CCKB-selective agonists (Huang et al, 1989).…”
Section: Discussioncontrasting
confidence: 61%
“…The data obtained in this study disagree with the observations made in isolated cell preparations wherein the CCKA selective antagonist, devazepide, was more powerful than L-365,260 at inhibiting the contractile responses to gastrin (Grider & Makhlouf, 1990). However, the data are in agreement with those obtained in a similar isolated cell preparation in which L-365,260 was more powerful than devazepide at blocking the contractile effects of CCKB-selective agonists (Huang et al, 1989).…”
Section: Discussioncontrasting
confidence: 61%
“…This non-selective action may account for the increasing antagonist activity and maximal depression seen with lorglumide as an antagonist of CCK-8 ( (Makovec et al, 1986;Bock et al, 1989;Hughes et al, 1990). However, different estimates of receptor binding affinity for these antagonists have been observed in other studies (Hill & Woodruff, 1989;Huang et al, 1989). In the present studies we have attempted to characterize gastrin/ CCK receptors by determining the apparent affinities of gastrin/CCK receptor antagonists in functional studies using isolated preparations of rat gastric mucosa (RGM) and guinea-pig ileum longitudinal muscle myenteric plexus (GPI).…”
Section: Antagonist Studiesmentioning
confidence: 96%
“…Previous reports have been inconsistent with respect of the involvement of specific CCKA-or CCKB/gastrin receptors in the contractile effects of CCK-8 and PG in guinea-pig stomach muscle (Bitar & Makhlouf, 1982;Huang et al, 1989;Menozzi et al, 1989;Grider & Makhlouf, 1990;Boyle et al, 1992;1993). Boyle et al (1993) have suggested that both were coupled to muscle contraction.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, the guinea-pig gastric muscle has been shown to contract in response to stimulation by both CCK and gastrin and the effects of the selective antagonists, devazepide and L-365260, have been examined (Bitar & Makhlouf, 1982;Huang et al, 1989;Menozzi et al, 1989;Grider & Makhlouf, 1990;Boyle et al, 1992Boyle et al, , 1993. The results of these studies are in conflict with respect to the involvement of specific CCKA-or CCKB/gastrin receptors in gastric smooth muscle contraction, in contrast to in vitro results in gastric acid secretory assays where CCK and gastrin only stimulate secretion by an action at CCKB/gastrin receptors (Spraggs & Patel, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation